Pengaruh Gaya Kepemimpinan Otoriter, Pemberian Insentif, Serta Lingkungan Kerja Terhadap Kepuasan Kerja - Johannes Maruli Tua; Zahera Mega Utama; Franky Franky (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the influence of authoritarian leadership style, providing incentives, and work environment on employee job satisfaction at the Protocol and Administration Bureau of the Ministry of Investment of the Republic of Indonesia. The research method used is a survey method with a quantitative approach. The population in this study was 49 employees at the Protocol and Administration Bureau of the Ministry of Investment of the Republic of Indonesia and sampling used saturated sampling techniques. Data collection tools using questionnaires. Data analysis techniques include tests of validity, reliability, classical assumptions, hypothesis tests (t test and F test), and determination coefficient tests. The results showed that authoritarian leadership style did not have a significant effect on job satisfaction, while the provision of incentives and work environment had a significant effect on job satisfaction. Simultaneously, the variables of authoritarian leadership style, incentivization, and work environment have a significant effect on job satisfaction. The contribution of authoritarian leadership style, incentives, and work environment to job satisfaction is 50%, while the remaining 50% is influenced by other variables outside the research model.